Prediction of Basic Commodity Prices at the Cooperative, SME, and Trade Office Using the Least Squares Method - Purwani, Desy; Samsudin, Samsudin (Journal of Applied Informatics and Computing, 2024)
The Cooperatives, Small and Medium Enterprises (SME), and Trade Office is responsible for managing national affairs related to maintaining the prices of basic commodities, including the implementation of technical instructions and regulations. A significant issue faced by the office is the lack of accessible information on estimated prices of basic commodities for both the public and government. This gap primarily stems from the absence of an information system in the Pematang Siantar City area capable of publishing these estimates. The purpose of this study is to design and develop a web-based system for predicting basic commodity prices, which will record annual price fluctuations for various basic commodities at the Cooperative, SME, and Trade Office. The findings of this study will provide policymakers with a better understanding of commodity prices in traditional markets within Pematang Siantar City, serving as a foundation for future price estimations. This is particularly relevant for market operations aimed at controlling unreasonable price increases. The Least Squares method was employed to calculate the estimated prices, with the system achieving a Mean Absolute Percentage Error (MAPE) of 14.20%, indicating that the system can predict market prices with a reasonable degree of accuracy.